2018
DOI: 10.1002/pep2.24099
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assembly of β‐turn motif‐connected tandem repeats of Aβ16‐22 and its aromatic analogs

Abstract: Self‐assembly of peptides and proteins into aggregates with a signature of cross‐β conformation is a hallmark of amyloids. Short peptides have provided important insights in understanding the various interactions that drive self‐assembly as well as the molecular architecture of the self‐assembled structures. The short amyloidogenic‐stretch of β‐amyloid, Aβ16‐22 (Ac‐KLVFFAE‐am), is a good model peptide to study the aspects of β‐amyloid fibril formation. In order to investigate how a turn‐supporting sequence cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The peptides were dissolved in dimethyl sulfoxide and purified on a reversedphase C18 column, as described previously. 43 The purified peptides were characterized by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The peptides were dissolved in dimethyl sulfoxide and purified on a reversedphase C18 column, as described previously. 43 The purified peptides were characterized by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The data were converted to mean residue ellipticity, as previously described. 43 Fourier Transform Infrared (FTIR) Spectroscopy. FTIR spectra were recorded for the 24 h old 2 mM peptide samples on a Shimadzu IRAffinity-1S Fourier transform infrared spectrophotometer on the attenuated total reflection (ATR) module equipped with a diamond ATR crystal.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each spectrum is the average of 8 scans. The data were converted to mean residue ellipticity ([θ] MRE ) as described elsewhere [16].…”
Section: Methodsmentioning
confidence: 99%
“…The modes of interaction in general are π-π stackings, hydrophobic associations, electrostatic interactions, and hydrogen-bonding. Various morphologies based on free and protected H-Phe-Phe-OH molecule (Ribeiro et al, 2019) and its analogs/derivatives forming fibrils (Reches and Gazit, 2005), vesicles (Guo et al, 2012), tubes (Reches and Gazit, 2006), wires (Huang et al, 2014;Marchesan et al, 2015b), plates (Tamamis et al, 2009), sheets, flakes , necklaces (Yuran et al, 2012) could be demonstrated by manipulating the stimuli and physical/chemical conditions (Adler-Abramovich and Datta et al, 2018Datta et al, , 2019. Concentration dependent ordered nanoarchitectures such as planar bilayers and other diverse shapes of vesicles, namely, discoid, toroid, ellipsoid, and pot-shaped, have been reported by Guo et al (2012).…”
Section: Dipeptides For Biologics Deliverymentioning
confidence: 99%